Pengaruh Mobilisasi Dini dan Pijat Oksitosin terhadap Involusi Uteri pada Ibu Post Partum - Yunik Windarti; Nur Zuwariah (STIKes Patria Husada Blitar, 2016)
One of the successful factors of uterine involution of postpartum mother is by doing early mobilization and oxytocin massage, but in fact, there are still a lot of reluctant postpartum mothers who did not do it. This research aims to analyze the influence of early mobilization and oxytocin massage on the uterine involution post partum mothers. Experimental analytical research was used with quasi experimental design â€œafter only with control quasi-experimental designâ€. The population was all 30 people of 2 hour to 7 day postpartum mothers in BPM Kusmawati, the large sample was divided into two groups: 15 treatment and 15 control groups taken with â€œpurposive samplingâ€ technique. The independent variable was early mobilization and oxytocin massage, while the dependent variable was uterine involution. Data were analyzed by using multiple logistic regression and wald test. The result showed that most of the postpartum mothers who did not do the early mobilization (70.6%) had abnormal uterine involution with OR = 13,200 (95% CI: 2.112 - 82.500), and most of them who did oxytocin massage almost entirely (80%) had normal uterine involution with OR = 11,000 (95% CI: 1.998 to 60.572). The conclusion of this research was the postpartum mother did not do early mobilization and oxytocin massage would cause in the uterine involution process running more and more badly. Health employees were expected to be more focus on monitoring the condition of postpartum mother and do oxytocin massage to assist uterine involution process.